Curacha ang babaeng walang pahinga - Roces,Rosanna; Jose, Jacklyn; Moreno, Ruby
A story about a torera (a live sex performer) who finds herself trapped in an anomalous game of association between sex, life and death, and its political equivalent of sleaze, subservicence and power in drug-addled world. Every night, she sets off to join her fellow toreras for a midnight show of fun and kitschy live sex act. In one tuning point of her life, she bumps into a long-lost friend, Myrna, a former torera, who seems to have a lost grip on life. Curacha makes it her personal mission to save Myrna as she does some sou-searching herself. In the end, we see traces of hope glimmering somewhere, somehow, in a manner that escapes the restless Curacha.-- Written by ledster